Self Efficacy, Role Conflict, and Job Satisfaction: A Mediation Analysis of Job Participation in Tourism Village Development Volunteers - Hafidza Nash’ul Amrina; Eka Adipura; Ari Kuntardina (Innovation Business Management and Accounting Journal, 2024)
This study investigates the relationship between self-efficacy, role conflict, job participation, and job satisfaction in the context of tourism village development volunteers. It also investigates the moderating role of Job Participation on the relationship between self-efficacy, role conflict and ambiguity, and job satisfaction. Data was collected from 225 volunteers and tourism village development managers in Bojonegoro Regency. The findings show that self-efficacy is positively related to job participation, while role conflict has no effect on job participation. Self-efficacy and role conflict also have a positive effect on job satisfaction. With regard to the moderating role of job participation, the findings show that there is an indirect relationship between self-efficacy and job satisfaction that is stronger with job participation. Additionally, the results of this study suggest that self-efficacy plays a crucial role in motivating tourism village development volunteers to actively participate in their roles, contributing to their overall job satisfaction. Furthermore, the findings highlight the importance of addressing and managing role conflicts to ensure a positive impact on job satisfaction among volunteers and tourism village development managers in Bojonegoro Regency.